NEW TECHNOLOGIES IN IMPLEMENTING THE OBLIGATION FROM ARTICLE 69 OF THE ACCOUNTANCY ACT - Siemiątkowski, Tomasz; Szczurowski, Tomasz (Człowiek w cyberprzestrzeni, 2020)
This paper discusses the impact of new technologies on the annual obligation of business to compile and submit to the registry court the corporate financial statements and other records detailed out by law. The aim of the article is not only to present relevant new legal solutions, but also to highlight the importance of applying new technologies in this area, both in the context of registration proceedings and business operations.